Poor reproductive success of polygynously mated female birds with obligatory bi-parental care: a result of deceptive behaviour of males? - Kujala Inga; Pöysä Hannu; Korpimäki Erkki (SPRINGER, 2022)
Social polygyny usually benefits males by increasing the number of offspring, whereas it is detrimental for females as they must share the resources provided by their mate. An intersexual conflict may exist in animals with obligatory bi-parental care, such as birds of prey, in which females incubate and brood, whereas males provision food for their families. Long-term ringing data from Eurasian kestrels (Falco tinnunculus) breeding in nest-boxes and data on density indices of main prey animals (voles) were collected during 1985-2013 in western Finland to study polygynous behaviour. Of 1294 males, 54 (4.2%) were encountered at two (53) or three (1) nests during the same breeding season. Polygyny occurred more frequently during years of high vole abundance. The distances between nests of corresponding primary and secondary females were greater (median 1010 m) than the distances from nests of primary females to the nearest vacant nest-box (median 455 m). Twenty-eight (53%) of 53 secondary females had nearest available monogamous male within 2 km from their nest-boxes, indicating that mating options were available. Secondary females produced 30% less fledged offspring than simultaneously laying monogamously paired females. The abundance of prey animals is apparently alleviating the effort of males mating with multiple females. Spacing out the nests of primary and secondary females implies deceptive behaviour in the nest-site selection of polygynous males. Contradicting the polygyny threshold model, reproductive success of secondary females was significantly reduced in comparison to monogamous females laying simultaneously. These results show that secondary kestrel females apparently made a maladaptive choice, likely because they were deceived to accept polygynous mating status during the courtship feeding period.
Significance statement
As dedicated parental effort of both the male and the female is vital to ensure the offspring survival amongst animals with obligatory bi-parental care, polygyny should be inherently a maladaptive mating strategy for females. However, regular social polygyny has been documented in at least 10% of bird species from ten orders. Previous studies on breeding success of polygynous birds of prey indicate reduced offspring production of secondary female partners with no apparent cause for females to choose polygynous males over other mating options. We showed that polygyny in Eurasian kestrels is frequent when food is abundant facilitating males to provision their two or more females during courtship feeding. Polygynous males space out their two nests thus attempting to hide their mating status from their secondary partners which suffer from their mate choice in form of poor reproductive success. Therefore, amongst the "cost of polygyny to females" hypotheses, the deceptive behaviour of males during courtship feeding appeared to be an apparent explanation for maladaptive mate choice of secondary females.